Learning logic, search and cracking through a number guessing game - Mok, Tsui-Qin; Mau, Wei-Ming; Wong, Calvin Weng-Kit; Koay, Kian-Wheng; Cheng, Meng-Jeat; Lee, Chien-Sing * (Asia-Pacific Society for Computers in Education, 2018)
This paper describes the development of a number guessing game aimed at playful learning of logic, search and cracking for the young. It can also be used to train memory and intelligent guessing for seniors. Theories and models utilized are Goals, Operators, Methods and Selection (GOMS), Norman’s 7 stages, and Schneiderman et. al’s design principles for user interface design. Findings among students indicate that the number guessing game is easy to use, and useful and that history and feedback are the most important design factors. This paper has managed to come out with an expected result where multitasking is required and player has to read and understand the meaning from the output to complete the game. We look forward to possibly designing for both children and seniors in the future by improving the game features without making the game become more complicated.